A Pneumatic Flexible Linear Actuator Inspired by Snake Swallowing - Yuyan Qi; Jiaqi Shao; Yongjian Zhao; Tong Niu; Yi Yang; Songyi Zhong; Shaorong Xie; Yangqiao Lin; Yang Yang (Advanced Science)
Abstract Soft robots spark a revolution in human–machine interaction. However, developing high‐performance soft actuators remains challenging due to trade‐offs among output force, driving distance, control precision, safety, and compliance. Here, addressing the lack of long‐distance, high‐precision flexible linear actuators, an innovative pneumatic flexible linear actuator (PFLA) is introduced, inspired by the smooth and controlled process observed in snakes ingesting sizable food, such as eggs. This PFLA combines a soft tube, emulating the snake's body cavity, with a pneumatically driven piston. Through the joint modulation of moving resistance and driving force by pneumatic pressure, the PFLA exhibits exceptional motion control capabilities, including self‐holding without pressure supply, smooth low‐speed motion (down to 0.004 m s–1), high‐speed motion (up to 5.6 m s–1) with low air pressure demand, and a self‐protection mechanism. Highlighting its adaptability and versatility, the PFLA finds applications in various settings, including a wearable assistive devices, a manipulator capable of precise path tracking and positioning, and rapid transportation in diverse environments for pipeline inspection and firefighting. This PFLA combines biomimetic principles with sophisticated fluidic actuation to achieve long‐distance, flexible, precise, and safe actuation, offering a more adaptive solution for force/motion transmission, particularly in challenging environments.